Crossing nerve transfer restores limb movement by reorganizing the cortico-rubro-spinal pathway in peripheral nerve injury - Zhen Pang; Yunuo Chen; Chuanjun Tong; Yiming Chen; Gaowei Lei; Zeyu Cai; Shuai Zhu; Yundong Shen; Zhifeng Liang; Jiayi Zhang; Fang Huang; Yuqiu Zhang; et al. (Cell Reports)
Summary: Peripheral nerves connect the central nervous system to the limbs. Crossing nerve transfer (CNT) promotes motor recovery after unilateral brain injury by inducing functional reorganization in central neural circuits. However, how specific circuits reorganize following peripheral nerve injury (PNI) under intact central pathways remains unclear. This study examines cortical neural circuit changes associated with motor recovery using a PNI mouse model with unilateral brachial plexus injury. CNT effectively restores motor function in the impaired forelimb. This cross-transferred pathway reconstructs sensory representations of the impaired forelimb in the ipsilateral sensorimotor cortex and enhances both inter- and intrahemispheric cortico-cortical projections, particularly interhemispheric projections from the ipsilateral to the contralateral sensorimotor cortices. Specifically, the contralateral motor cortex functionally reinnervates the injured forelimb through regenerated corticorubral and rubrospinal projections rather than corticospinal projections. These findings elucidate the circuit mechanisms underlying CNT-induced forelimb recovery and suggest potential targets for promoting functional restoration in PNI.